دور الإدارة المعرفة في تحقيق الأداء المتميز للمؤسسة الاقتصادية - عبد المجيد, كروش; عيسى, كروش; نعيمة, منصوري; حمزة, نسيب (University of eloued جامعة الوادي, 2022)
تهدف هذه الدراسة إلى الكشف عن أثر إدارة المعرفة على الأداء في المؤسسة الاقتصادية، من خـلال التعريـف بـإدارة المعرفة ومنهجيتها، وتقديم الإطار النظري للأداء في المؤسسة، وإبراز تأثير الإدارة الفعالة للمعرفة علـى مكونـات الأداء غيـر الملموس في المؤسسة، والمتمثلة في العاملين والتعلم والرضا الوظيفي، والعمليات الداخلية والإبداع، بمـا يضـمن تحقيـق الأداء المتميز في النهاية بالنسبة للمؤسسة, وقد استخدمت الدراسة المنهج الوصفي التحليلي لمعالجة موضوع البحث، وقد خلصت إلى أهمية إدارة المعرفة في التأثير الإيجابي على كفاءة وفعالية العمليات الداخلية، وفي تحقيق الرضا الـوظيفي للعـاملين والرفع من مستوى تعلمهم"This study aims to reveal the impact of knowledge management on the performance in the economic establishment, through the definition of knowledge management and its methodology, and providing the theoretical framework of the performance of the enterprise, and to highlight the impact of the effective management of knowledge on the components of the performance intangible in the enterprise, which represent the workers, learning and job satisfaction, and processes Interior and creativity, so as to ensure the achievement of outstanding performance in the end. The study used the descriptive analytical approach to address the subject of research, as concluded in the last by the importance of knowledge management in a positive impact on the efficiency and effectiveness of internal processes, and achieve job satisfaction for workers and raise the level of learning, through effective steps for knowledge management within the organization. "
ماستر ادارة اعمال
Keywords: إدارة المعرفة، الأداء، الكفاءة، التميز، العاملين.; knowledge management, performance, efficiency, excellence, employment.